Reading London's Suburbs From Charles Dickens to Zadie Smith - Pope, G. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
A study of London suburban-set writing, exploring the links between place and fiction. This book charts a picture of evolving themes and concerns around the legibility and meaning of habitat and home for the individual, and the serious challenges that suburbia sets for literature.